Global Industrial Efficiency Revolutionized by Automated Lathe: Efisiensi Industri Global yang Direvolusi oleh Mesin Bubut Otomatis - Rokhman, Fatori; Fahruddin, A'rasy (Indonesian Journal of Innovation Studies, 2024)
The implementation of an automatic lathe, utilizing hydraulic drive and PLC programming, stands as a significant advancement in industrial engineering aimed at augmenting productivity while circumventing additional labor requirements. Through meticulous research, it was discerned that the predominant issue plaguing the production process was the occurrence of stoppages due to irregular or unstable dimensions in the output, particularly concerning the Item Bush K0JA Left. Employing methodologies such as SIPOC analysis and the 4M framework revealed that the root cause primarily stemmed from machine-related factors, exacerbated by fluctuations in the installation, resulting in misalignments and subsequent dimension inaccuracies. Addressing this, a targeted intervention involving the addition of locking bolts to the material fixture mitigated the stoppage occurrences significantly, with the operator rectifying positioning irregularities on average 1200 minutes per month. This intervention not only enhanced operational efficiency but also yielded tangible cost savings, amounting to Rp 578,000 monthly or Rp 6,936,000 annually, attributed to the prevention of production downtime. The implications of this study underscore the importance of proactive measures in streamlining manufacturing processes, thereby optimizing resource utilization and economic viability. Further research avenues could delve into the optimization of maintenance protocols for automated machinery and the exploration of advanced sensor technologies to preemptively detect dimensional inconsistencies, thus bolstering overall production resilience and efficacy. Highlight: Advanced machinery integration boosts manufacturing efficiency. Root cause analysis reveals process optimization insights. Cost savings demonstrate practical impact of production enhancements. Keywoard: Automatic lathe, Industrial engineering, Productivity enhancement, Dimensional accuracy, Cost savings